2011
DOI: 10.1103/physrevlett.107.035502
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Limiting Thickness of a Thin Oxide Layer on Al(111) with Oxygen Gas Pressure

Abstract: We report an x-ray photoelectron spectroscopy study of the oxidation of Al(111) surfaces at room temperature, which reveals that the limiting thickness of an aluminum oxide film can be tuned by using oxygen pressure. This behavior is attributed to a strong dependence of the kinetic potential on the oxygen gas pressure. The coverage of oxygen anions on the surface of the oxide film depends on the gas pressure leading to a pressure dependence of the kinetic potential. Our results indicate that a significantly la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 30 publications
10
70
0
Order By: Relevance
“…Moreover, the magnitude of the Mott potential agrees with experimental estimates [2,5]. It is interesting to note that, although there is a slow decrease of the Gibbs free energy of the adsorbed oxygen molecule, the Mott potential does not display such behavior.…”
supporting
confidence: 74%
See 4 more Smart Citations
“…Moreover, the magnitude of the Mott potential agrees with experimental estimates [2,5]. It is interesting to note that, although there is a slow decrease of the Gibbs free energy of the adsorbed oxygen molecule, the Mott potential does not display such behavior.…”
supporting
confidence: 74%
“…The calculated limiting thickness at 1 Torr is only slightly larger than the one recently measured by Zhou et al [5,6] The minor discrepancy (roughly one trilayer) can be attributed to the simplification of the structural models as well as to the well known overbinding of adsorption energies of O 2 predicted by the current version of DFT [16]. It should be noted that the initially formed oxide layers in the experiment appear to be disordered [5], which only gradually transform into crystalline α-Al 2 O 3 [29]. However, we have explicitly confirmed that our conclusions are not critically dependent on the chosen phase of alumina or the presence of defects in the film [30].…”
mentioning
confidence: 51%
See 3 more Smart Citations